Perineal reconstruction with musculocutaneous flap rectus abdominis - Canessa, César; Segura, Daisy; Jacobo, Oscar; Gómez del Valle, María José; Pérez, Gabriela (Cirugía del Uruguay, 2003)
We present two consecutive patients operated for advanced carcinoma of the anus by abdominoperineal excision. Both cases resulted in wide perineal wound closed primarily with transposition of the rectus abdominis myocutaneous flap. This study analyse anatomic and technical main aspects of the surgical procedure.